Dominant role of corporate image and trust in building customer satisfaction in Islamic life insurance - Jubaidi, Jubaidi; Pangestu, Krismohadi; Riyandi, Ahmad; Gessa, Derry Royan (LPPM ISNJ Bengkalis, 2025)
Purpose – This study analyses the influence of service quality, corporate image, customer value, and trust on customer satisfaction at PT. Asuransi Jiwa Syariah X Samarinda branch. Method – This study uses a quantitative approach, where the data comes from questionnaires distributed to 100 customers. The data analysis technique uses multiple linear regression analysis through the SPSS 22 program. Findings – The study's results indicate that, partially, corporate image and trust positively affect customer satisfaction, while service quality and value do not affect customer satisfaction. Implications – This study has practical implications for Islamic insurance companies, especially in improving corporate image and building customer trust. Theoretically, this study strengthens the theory that image and trust affect customer satisfaction.